A Technical and Practical Comparison of Traditional and Neural Rendering Methods in Games - Lin, Daiyao (Transactions on Computer Science and Intelligent Systems Research, 2025)
Rendering technology, a significant component of modern computer graphics, plays a vital role in the game field. With the growing demand for visual realism and real-time performance in game development, rendering technology has been continuously developed and optimized. This paper presents a comparative study of the three techniques - rasterization, ray tracing, and neural rendering- within an interactive gaming environment. By analysing their fundamental principles and practical applications in the gaming field, the analysis highlights each technique’s respective advantages, limitations, and domains of applicability within the gaming field. Rasterization is widely adopted in real-time and small-scale games due to its high rendering efficiency and low hardware demands. Conversely, ray tracing provides a more realistic light simulation. This technology is increasingly used to develop games with high graphics quality requirements. Neural rendering leverages artificial intelligence (AI) techniques to balance rendering quality and efficiency, showing promising applications. Furthermore, this study raises expectations for the evolving convergence of multiple rendering techniques.